(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The study seeks to clarify the role of International Auditing Standard No. (320) of the relative importance in determining responsibility for planning and implementing the process of auditing financial statements and expressing neutral technical opinion through the analytical procedures of the auditor, whose responsibility is to obtain appropriate and reliable audit evidence that helps the auditor to form a general conclusion about whether The financial statements were consistent with the auditor’s understanding of the entity. The relative importance contributes to defining the important accounts that help to set priorities for the auditor to set the necessary analytical procedures for these accounts. One of the most important conclusions of the study is to focus on the direct relationship between materiality and the amount or volume of evidence at the level of the financial statements, so the greater the level of materiality the greater the evidence to be obtained, but at the level of the items, the relationship between the level of materiality of the item and the evidence of proof is a positive relationship, which is reflected On the analytical procedures. Among the most important recommendations reached by the study is to determine the analytical procedures according to the above relationship to the relative importance and evidence of evidence and disclosure of the analytical procedures related to financial indicators within the financial statements of companies in the Iraqi environment and the need to include Iraqi audit evidence, a special audit guide of materiality. Key words: materiality, analytical procedures